Psychometric Properties of the Dyadic Coping Inventory: Systematic Review - Wanderson Ricardo Nepomuceno; Aline da Silva Gonçalves; José Augusto Evangelho Hernandez (Interpersona: An International Journal on Personal Relationships, 2022)
This systematic review study analyzed the evidence of validity of the Dyadic Coping Inventory’s internal structure. This instrument measures the quality of communication and the strategies of marital coping in face of the stress experienced. Stress can affect the stability and maintenance of marital relationships depending on how it is faced by the couple. The measure is a reduced version of the Dyadic Coping Questionnaire and has been applied to various cultural contexts. This research study was registered at the International Prospective Register of Systematic Reviews database. Searches for publications were made on the Capes' Portal Periódico and Google Scholar, not refining the results. Two independent researchers selected, extracted, and evaluated the data. For the validity analysis of the internal structure, the Standards for Education and psychological Testing were consulted. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses Statement was used to summarize the review. Of the 722 studies found, 15 were selected, from the Scopus, Web of Science, John Wiley & Sons, Directory of Open Access Journals, DergiPark, Pubmed and Taylor & Francis Online databases. All articles included were quantitative, cross-sectional and peer reviewed studies, mostly carried out in Europe and in 14 different languages. Despite variations in the number of factors and items, the instrument has shown to be stable and invariant across genders and cultures. These results suggested a reliable score to measure Dyadic Coping. This review can contribute to clinical practice and research in marital and family relationships.